3PC-010 Assessment of Chemfort (OnGuard, US) syringe adaptor lock fitted with Luer lock syringes to container integrity standards (NHS, UK) supporting dose banding of cytotoxic drugs. (23rd March 2022) - Wilkinson, A; Ozolina, L; Walker, K; Machnikova, R; Allwood, MC; Bhogal, N; Pegg, K
Abstract : Background and importance: Disposable syringes are used as final containers in dose banding of cytotoxic products within pharmacy aseptic services. Closed system transfer devices (CSTDs) could mitigate exposure to cytotoxic drugs while maintaining drug sterility. There is a paucity of container integrity data that satisfies standards (National Health Service (NHS)) supporting the use of CSTDs as part of storage devices in aseptic services. Aim and objectives: Study aim: to satisfy container integrity requirements using Brevundimonas diminuta with an extended contact time of 14 days at 30°C–35°C (NHS, YCD), supporting the use of Chemfort (OnGuard) with a range of Luer lock (LL) syringe sizes as long-term storage devices in UK dose banding. Material and methods: Chemfort (Simplivia Healthcare) SAL integrity tested with Luer lock syringes: 1 mL, 20 mL and 60 mL. Each SAL+LL syringe combination (n=20) was filled with Tryptone Soya Broth (TSB) media puncturing the SAL septa (n=3). Devices were: immersed in TSB inoculated with 24-hour culture of B. diminuta (media:culture ratio 100:1) covering the SAL+LL syringe hub, incubated for 14 days at 30°C–35°C and inspected for growth. Each combination SAL/syringe size (n=20) was: filled with MilliQ water, sealed, submerged in 0.4% w/v methylene blue (MB) dye, rotated at 45 rpm for 2 hours and inspected (absorbances measured at 660 nm on a plate reader) (Epoch, Biotek UK). Limit of detection (LOD) for MB dye was 0.010 mAu at 660 nm. Results: Chemfort SAL/syringe combinations showed no microbial growth at the end of the test demonstrating container integrity. Positive controls (n=2) produced growth after inoculation with <100 cfu of B. diminuta incubated for 3 days at 30°C–35°C. Chemfort SAL/LL syringes (n=60) tested with MB dye had <LOD absorbances at the end of the test demonstrating 100% integrity. Positive controls (n=3) for each syringe size resulted in dye ingress with absorbances >LOD confirmed spectrophotometrically. Conclusion and relevance: Chemfort (OnGuard) SAL/LL syringe combinations (n=120) with septa punctures (n=3) prior to testing conformed to container integrity requirements (NHS) for physical and microbiological (even when submerged in B. diminuta with extended contact for 14 days at 30°C–35°C) syringe integrity supporting their use within pharmacy aseptic services and dose banding. References and/or acknowledgements: 1. Santillo M. Protocols for the integrity testing of syringes. NHS Pharmaceutical Quality Assurance Committee (accessed 13 October 2021). https://www.sps.nhs.uk/wp-content/uploads/2013/07/NHS-PQAC-YCD-Integrity-Testing-of-Syringes-2013-2nd-Edn1.pdf Conflict of interest: No conflict of interest